1981
DOI: 10.1128/aac.19.5.917
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of mycoplasmas by long-chain alcohols

Abstract: In this report, we describe the inhibitory activity of long-chain alcohols on the growth of Mycoplasma gallisepticum and Mycoplasma pneumoniae. Peak inhibition was recorded with saturated primary alcohols (64 ,uM) varying in chain length from 16 to 19 carbon atoms. The unsaturated alcohols (oleyl, linoleyl, and linolenyl) and the secondary alcohol (pentadecan-2-ol), when employed in the same test conditions, were considerably less effective growth inhibitors than the primary saturated alcohols. Stearic and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Alcohols mainly act by forming hydrogen bonds with proteins, leading to loss of structure and function and molecule coagulation (McDonnell 2007). It has already been demonstrated that various alcohols inhibit growth and trigger rapid lysis of mycoplasma (Razin and Argaman 1963; Fletcher et al. 1981); this was confirmed in our study with complete inactivation of each mycoplasma species after 5‐min exposures to 70% ethanol.…”
Section: Discussionsupporting
confidence: 89%
“…Alcohols mainly act by forming hydrogen bonds with proteins, leading to loss of structure and function and molecule coagulation (McDonnell 2007). It has already been demonstrated that various alcohols inhibit growth and trigger rapid lysis of mycoplasma (Razin and Argaman 1963; Fletcher et al. 1981); this was confirmed in our study with complete inactivation of each mycoplasma species after 5‐min exposures to 70% ethanol.…”
Section: Discussionsupporting
confidence: 89%